Association between solitary keratoacanthoma and cigarette smoking: A case-control study - Miot, Hélio Amante [UNESP]; Miot, Luciane Donida Bartoli [UNESP]; Costa, Ana Laura Bastos da [UNESP]; Matsuo, Cristiane Yuri [UNESP]; Stolf, Hamilton Ometto [UNESP]; Marques, Mariângela Esther Alencar [UNESP] (My University, 2006)
Solitary keratoacanthoma (KA) is a common benign epithelial tumor of the skin characterized by rapid growth and a tendency toward spontaneous regression. The exact etiology and classification of KA are a matter of debate. Smokers also seem to be more affected than persons who never smoke. The objective of this study was to evaluate the association between solitary KA and smoking habit. A case-control study involving 78 patients diagnosed with KA and 199 controls from the related community was performed to evaluate the association between cigarette smoking and KA. A higher smoking prevalence was noted in cases (69.2 %) than controls (21.6 %) and the odds ratio adjusted for sex and age was 9.1 (95 % CI 4.9 to 17.1, p< 0.01). The mean tumoral diameter at surgery and the site of involvement was not statistically related to smoking. These findings suggest that cigarette smoking is associated with the development of KA. © 2006 Dermatology Online Journal.
Keywords: adult; cigarette smoking; controlled study; epithelium tumor; human; keratoacanthoma; major clinical study; prevalence; risk factor; skin cancer; smoking habit; tumor volume